Signature of type-II Weyl semimetal phase in MoTe 2 - Jiang, J.; Liu, Z. K.; Sun, Yan; Yang, H. F.; Rajamathi, C. R.; Qi, Y. P.; Yang, L. X.; Chen, C.; Peng, Han; Hwang, C. -C.; Sun, S. Z.; Mo, S. -K.; et al. (Nature Communications, 2017)
Topological Weyl semimetal (TWS), a new state of quantum matter, has sparked enormous research interest recently. Possessing unique Weyl fermions in the bulk and Fermi arcs on the surface, TWSs offer a rare platform for realizing many exotic physical phenomena. TWSs can be classified into type-I that respect Lorentz symmetry and type-II that do not. Here, we directly visualize the electronic structure of MoTe 2, a recently proposed type-II TWS. Using angle-resolved photoemission spectroscopy (ARPES), we unravel the unique surface Fermi arcs, in good agreement with our ab initio calculations that have nontrivial topological nature. Our work not only leads to new understandings of the unusual properties discovered in this family of compounds, but also allows for the further exploration of exotic properties and practical applications of type-II TWSs, as well as the interplay between superconductivity (MoTe 2 was discovered to be superconducting recently) and their topological order.
CRIS-Team Scopus Importer:2022-04-14